1988
DOI: 10.1002/ijc.2910410202
|View full text |Cite
|
Sign up to set email alerts
|

Formation of dna adducts and water‐soluble metabolites of benzo[a]pyrene in human monocytes is genetically controlled

Abstract: Formation of DNA adducts and of water-soluble metabolites was studied in monocytes of 86 first-degree relatives of 15 families. Tests were performed with blood monocytes using (G-3H)-benzo[a]pyrene as a model pro-carcinogen. Variance analysis revealed significantly higher inter-familial than intra-familial variations. From these data we conclude that the formation of DNA adducts is genetically controlled. Therefore the enhanced formation of benzo[a]pyrene DNA adducts in lung cancer patients found in earlier st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…This is in line with the assumption that inter-individual variation in carcinogen metabolism is an important determinant of cancer susceptibility (Harris, 1991;Nowak et al, 1988). Theoretically, some arguments in favor of this model can be given; for example, some people drink and smoke excessively but never develop a tumor while others who drink and smoke less develop a tumor at an early age.…”
Section: Discussionmentioning
confidence: 55%
“…This is in line with the assumption that inter-individual variation in carcinogen metabolism is an important determinant of cancer susceptibility (Harris, 1991;Nowak et al, 1988). Theoretically, some arguments in favor of this model can be given; for example, some people drink and smoke excessively but never develop a tumor while others who drink and smoke less develop a tumor at an early age.…”
Section: Discussionmentioning
confidence: 55%
“…Gupta et al (1988) demonstrated the capacity of human peripheral blood lymphocytes to in vitro metabolize a number of carcinogens, including B[α]P, to their DNA binding species and high inter-individual variations (up to 62 fold) in binding capacity of reactive PAH derivatives were observed. This variation in B[a]P related DNA adduct formation in vitro was found to be genetically controlled (Nowak et al, 1988) and may be indicative for individual differences in lung cancer susceptibility (Hawke et al, 1986;Nowak et al, 1992). However, WBC are not necessarily target cells for PAH or the most sensitive cells for DNA adduct formation and the question remains whether these cells provide a reliable estimate of PAH exposure in vivo.…”
Section: Studies In Humansmentioning
confidence: 99%
“…The metabolic activation process produces DNA adducts, which are critical in the carcinogenic process because they cause mutations in important growth control genes, such as KRAS and p53 (4, 9, 10). The metabolic activation of PAH to DNA adducts varies widely among individuals (11)(12)(13)(14)(15)(16)(17). These well-established facts lead to the major hypothesis that smokers who efficiently metabolically activate PAH will be at a higher risk for lung cancer.…”
Section: Introductionmentioning
confidence: 99%